Analisis efektivitas revitalisasi pasar angso duo Jambi terhadap pendapatan pedagang sayuran - Aqil , Muhammad; Nurjanah, Rahma; Umiyati, Etik (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2025)
This study is entitled an analysis of the effectiveness of the revitalization of the Angso Duo Jambi market on the income of vegetable traders. The objectives of this study are 1) To find out and analyze the characteristics of vegetable traders in the Angso Duo Jambi Market. 2) To find out and analyze the difference in income of vegetable traders before and after the revitalization at Angso Duo Jambi Market. 3) To find out and analyze the effect of revitalization effectiveness on the income of vegetable traders in the Angso Duo Jambi market. The data sources used are primary data in the form of questionnaire results and interviews. The research method used was quantitative descriptive and used paired sample test tools and simple linear regression, by giving questionnaires to 89 respondents. The results of the study showed that there was a difference in the income of vegetable traders before the revitalization of the market and the income after the revitalization of the Jambi City angso duo market. The effectiveness of market revitalization has a negative effect on the income of vegetable traders in the Jambi City angso duo market.